Among the Digital Luddites - Stiles, T. J. (The Columbia Journal of Law & the Arts, 2015)
I’m here to throw empirical salt on theory’s slug. In discussions of copyright or the literary marketplace, there is too much generalization. We often see the experience of one author with one book presented as a template for everyone, but book publishing doesn’t work that way. Each book is a unique product. One can take ten years to write, another ten weeks. It might be filled with photos and maps, or with none. What is true for one author will not be true for another. I am a self-employed author of serious nonfiction in the commercial marketplace. My world is summed up by an episode of The Simpsons, titled “The Front.” Bart and Lisa take Grandpa Simpson to visit the studio that makes “Itchy and Scratchy” cartoons; they’ve been submitting freelance scripts in Grandpa’s name. The studio chief says to Grandpa, “Are you sure you’re a writer? You’re so old!” Grandpa replies, “Where’s my check!” The studio chief says, “Oh, you’re a writer all right.” Self-employed writers can’t spend five minutes together without discussing money. If you think it’s because we’re greedy, let me quote The Aviator: “The only reason you don’t care about money is that you’ve always had it.” Like all of you, we want to make a living doing what we do best. We know we might fail, but we want to be able to try. But we face a structural problem. We are disaggregated individuals in a global economy dominated by large institutions that feel free to take advantage of us: huge corporations and sometimes, sadly, even universities. But our shared culture depends upon individual voices. Dissent comes from outside institutional thinking; creativity comes from the individual, often in opposition to majority opinion.